Implementasi Permendagri Nomor 86 Tahun 2017 Dalam Penyusunan Perencanaan Pembangunan Daerah Di Kabupaten Tulungagung - Devi Ismawati; Suwarno Suwarno; Teguh Pramono; Imam Fachruddin; Muhamad Chairul Basrun Umanailo (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
This study describes the implementation of Permendagri 86/2017 in preparing development plans in Tulungagung Regency and its supporting and inhibiting factors. The research uses descriptive qualitative methods to construct data findings in the field with various relevant theories. The data collection technique uses interviews with selected informants. Data analysis uses an interactive model: data collection, condensation, data presentation and drawing conclusions. The results of the study found that the implementation of Permendagri 86/2017 in the preparation of regional development planning in Tulungagung Regency has been going well but not optimal, judging from the factors that influence policy implementation according to the theory of George C. Edwards III, namely: Communication has been going well at the level technical implementation, but needs to be improved at the leadership level; Resources that have been fulfilled in quantity but need to be increased in terms of the quality of these resources, especially human resources; The trend has been going well, the attitude of the implementor is to provide support, there is an incentive; and The bureaucratic structure is running well, the implementor is carrying out the task well, but not yet supported by the SOP.